COMPARATIVE STUDY ON THE OBTAINING TECHNOLOGY INFLUENCE ON THE STRUCTURE AND PROPERTIES OF METAL CROWNS MADE OF Co-Cr-Mo ALLOY - Nicolcescu Pantelie; Nazem Daewod; Marian Miculescu; Marius Tudorache; Iulian Antoniac; Doriana Agop-Forna (Romanian Society of Oral Rehabilitation, 2023)
The aim of this paper is to highlight the influence of the dental prosthetic works obtaining technology on their structure and properties. Three metal skeletons of dental crowns made of Co-Cr-Mo alloy were developed by three different technologies: classical casting, milling and selective laser melting. Surface properties, μCT investigations, microstructure and mechanical test were used to comparatively investigate the obtained structures. At the same time, the experimental investigations carried out in this paper show that the technology of obtaining Co-Cr alloys can influence the structure and properties of materials. Within the limits of the presented study, it can be stated that the selective melting technology of Co-Cr-Mo alloys is preferred in dental restorations due to improved properties, longevity, but also good interaction with the oral environment.